The Role of the Away Rotation in Otolaryngology Residency. (28th March 2017) - Villwock, Jennifer A.; Hamill, Chelsea S.; Ryan, Jesse T.; Nicholas, Brian D.
Abstract : Objective: To determine the availability and purpose of away rotations during otolaryngology residency. Study Design: Cross‐sectional survey. Setting: Otolaryngology residency programs. Subjects and Methods: An anonymous web‐based survey was sent to 98 allopathic otolaryngology training program directors, of which 38 programs responded. Fisher exact tests and nonparametric correlations were used to determine statistically significant differences among various strata of programs. A P value of <.05 was considered statistically significant. Results: Thirty‐nine percent (n = 38) of queried programs responded. Mandatory away rotations and elective away rotations were both present in 6 of 38 programs (16%). Neither number of faculty ( P =. 119) nor residents ( P =. 88) was predictive of away rotation. Away rotations were typically >151 miles from the home institution and typically used to address deficiencies in clinical exposure (67%) or case volume (50%). Participants of mandatory away rotations were universally provided housing, with other consideration such as stipend (33%), relocation allowance (33%), or food allowance (16%) sometimes offered. In contrast to mandatory rotations, half of elective rotations were to obtain a unique international mission trip experience. Nearly one‐third of surveyed program directors (29%) would consider adding an away rotation to their curriculum in the next 3 years. Conclusions: Mandatory and elective away rotations play a role in a small, but not insignificant, number of training programs. The rationale for these rotations is variable. Given that nearly one‐third of program directors would consider adding an away rotation in the near future, further research into components of a meaningful away rotation and how to optimize the away rotation experience is warranted.